Model Pengembangan Kemampuan Bahasa dan Sosialisasi Anak di Paud Aliifah Medan Marelan Selama Masa Pandemi Covid-19 - Mulia, Ana; Deli, Aswaniah Ugi; Lubis, Eny Irmayanti; Junaida, Junaida (Prodi PIAUD STAI Sumatera Medan, 2021)
This study aims to analyze (1) the AUD language skills development model, (2) the AUD socialization skills development model, (3) the importance of the role-playing method to the AUD ability development and socialization. This research was carried out by PAUD Aliifah Medan Marelan. The research method used is qualitative with a descriptive study approach. The results of the study indicate that the AUD language skills development model which is applied is reading textbooks, communicating with teachers and other friends, listening to stories, writing simple letters and numbers, telling stories about experiences and dreams. Then the model for developing early childhood socialization skills includes playing with family, talking by telephone, teachers and parents as role models, playing outside the home. The urgency of playing a role in the development of ability and socialization of AUD is to train children's skills in communicating with others so that they are skilled in systematizing words, and are skilled in processing the right vocabulary for others when speaking.